Sosialisasi Peningkatan Pemilahan Sampah Dari Kelas Sampai Ke Halaman Sekolah Di SMKN 7 Malang - Wulandari, Lies Kurniawati; Mundra, I Wayan; Hardianto, Hardianto; Munasih, Munasih; Roostrianawaty, Nenny; Gai, Ardiyanto Maksimilianus (STIE Malangkucecwara, 2024)
The development of the current era of globalization has led to technological advances in various fields, both in terms of economy, social, education, and health. Technological advances have positive and negative impacts on the environment. One of the negative impacts of technological advances on the environment is environmental damage which results in a decrease in the quality of the environment. The environment is a unified system where there is a mutual interaction between living things, objects, and resources. A person's attitude can determine the good and bad conditions and conditions that occur in the surrounding environment. The environment must be kept clean and beautiful with a full sense of responsibility and have sensitivity in protecting the environment. However, based on the results of observations, it is known that the attitude of caring for students at one of the SMKN in Malang City is still lacking. To foster an attitude of caring for the environment, community service is carried out which aims to provide education on environmental awareness, especially SMKN students. The results obtained from this community service turned out to be very beneficial for students, they became more aware of protecting and maintaining the environment around them.